The Relationship between Social Media Usage and Mental Well-Being among Young Adults - Saima Majeed, Adeena Ateeque, Momena Rehman, Aman Riaz, Aster Paul (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The use of social media has grown rapidly over the past decennium and a half, however, not much research is conducted on it to identify its correlation with mental well-being and its effects. Aim: To determine the correlation between social media usage and mental well-being in young adults. Study design: Cross Sectional study. Methodology: Data was collected using convenient sampling. This study includes a sample size of 215 young adults, 108 men, and 107 women, from two universities in Lahore, Pakistan, aged between 18 -25 years. Two instruments were used in this study to measure the variables, the Social Networking Usage questionnaire, and Warwick-Edinburgh Mental Well-being Scale. Data was evaluated by using SPSS version 24. Pearson’s correlation and independent sample t-test were applied with p-value < 0.05 as significant. Results: Findings indicated a significant positive relationship between all dimensions of social media usage including academic, socialization, entertainment, and information. High mean scores indicated that research participants mostly use social media for academic purposes. There was not a statistically significant relationship that could be seen between social media usage and mental well-being. Gender differences were found only related to mental well-being where men scored high as compared to women with a significance of 0.01 level. Practical Implication: Present study results raised the idea of examining other mediating or moderating factors between the connection between social media platforms usage and mental well-being. Not only the time but the content and purpose of social media should also be considered while establishing the direction of the relationship. Conclusion: It was concluded that young adults’ use of social media has not an inverse connection with mental health, and they mostly use it for academic purposes. However, men and women are different on the mental well-being scale, and men with high well-being reported for the present sample. Key words: Social Media, Correlation, Mental Well-Being, Depression and Self-Esteem.